Solid electrolytic capacitor and method for manufacturing solid electrolytic capacitor

A dual-layer electrolyte structure in solid electrolytic capacitors, with a covalently bonded ion-conducting layer and a conductive polymer electron-conducting layer, addresses the need for miniaturization and capacitance enhancement, ensuring high capacitance ratio and reliability.

CN119230301APending Publication Date: 2024-12-31TOKIN CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410811863.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-29
Filing Date
2024-06-21
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The challenge of miniaturizing solid electrolytic capacitors while maintaining or enhancing their capacitance per unit volume has become necessary due to the trend of smaller electronic devices.

Method used

A solid electrolytic capacitor design featuring a first ion-conducting electrolyte layer and a second electron-conducting electrolyte layer, with the first layer being covalently bonded to the dielectric layer using a silane coupling agent to prevent ionic liquid outflow, and the second layer being formed with conductive polymers to enhance conductivity.

Benefits of technology

The design improves the apparent capacitance ratio and prevents the outflow of ionic liquids, maintaining capacitor performance and reducing characteristic failures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230301A_ABST
    Figure CN119230301A_ABST
Patent Text Reader

Abstract

The invention relates to a solid electrolytic capacitor and a preparation method thereof. A solid electrolytic capacitor according to an aspect of the present disclosure includes an anode member made of a valve metal; a dielectric layer formed over the anode member; and a solid electrolyte layer formed over the dielectric layer, in which the solid electrolyte layer includes: a first electrolyte layer formed over the dielectric layer; and a second electrolyte layer formed over the first electrolyte layer; wherein the first electrolyte layer is an ion conducting electrolyte layer, and the second electrolyte layer is an electron conducting electrolyte layer.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to and the benefits of Japanese Patent Application No. 2023-106818 filed in Japan on June 29, 2023, the entire contents of which are incorporated by reference into this application. Technical Field

[0003] The present disclosure relates to a solid electrolytic capacitor and a method for manufacturing the solid electrolytic capacitor. Background Art

[0004] In recent years, solid electrolytic capacitors have been widely used in various fields, such as the field of electronic devices. Japanese Unexamined Patent Application Publication No. H6-69082 discloses a solid electrolytic capacitor technology in which a conductive polymer is used as a solid electrolyte. Summary of the invention

[0005] As described above, solid electrolytic capacitors have been widely used in various fields, such as the field of electronic equipment. In recent years, as the size of electronic devices has become smaller and smaller, it is necessary to miniaturize solid electrolytic capacitors. Therefore, since it is necessary to miniaturize solid electrolytic capacitors while maintaining the capacitance of solid electrolytic capacitors, it is necessary to increase the capacitance appearance ratio per unit volume of such solid electrolytic capacitors.

[0006] In view of the above problems, an object of the present disclosure is to provide a solid electrolytic capacitor capable of improving its apparent capacitance ratio, and to provide a method for manufacturing such a solid electrolytic capacitor.

[0007] A solid electrolytic capacitor according to one aspect of the present disclosure includes: an anode member made of a valve metal; a dielectric layer formed on the anode member; and a solid electrolyte layer formed on the dielectric layer. The solid electrolyte layer includes: a first electrolyte layer formed on the dielectric layer; and a second electrolyte layer formed on the first electrolyte layer. Further, the first electrolyte layer is an ion-conducting electrolyte layer, and the second electrolyte layer is an electron-conducting electrolyte layer.

[0008] A method for manufacturing a solid electrolytic capacitor according to one aspect of the present disclosure includes: a first step of forming a dielectric layer on an anode member made of a valve metal; and a second step of forming a solid electrolyte layer on the dielectric layer. The second step includes: a third step of forming a first electrolyte layer on the dielectric layer; and a fourth step of forming a second electrolyte layer on the first electrolyte layer. Further, the third step includes forming a layer containing a material represented by formula (1) shown below on the dielectric layer.

[0009] [Formula 1]

[0010]

[0011] Note that M in the formula (1) shown above represents a valve metal atom.

[0012] R 1+ a functional group representing at least one type of cation selected from the group consisting of imidazolium derivatives, pyrrolidinium derivatives, piperidinium derivatives, pyridinium derivatives, morpholinium derivatives, ammonium derivatives, derivatives and sulfonium derivatives, and R 1+ There is a carbon chain with a carbon number of 1 to 20 between the functional group of the cation and the Si molecule, and there is an ester bond, an ether bond, an amide bond, an imide bond, a carbon-carbon unsaturated bond, a carbon ring, or an interchain heterocycle.

[0013] In the formula (1) shown above, R 2 represents one of the following: a hydrogen atom, a carbon chain having a carbon number of 1 to 4, a valve metal atom, or a polymer in which the materials represented by the formula (1) are each polycondensed and connected to each other through -Si-O-Si-.

[0014] In the formula (1) shown above, X- represents at least one type of anion selected from the group consisting of chloride, bromide, iodine, acetic acid, decanoic acid, sulfuric acid, lactic acid, nitric acid, benzoic acid, hydroxide, methyl sulfate, methanesulfonic acid, ethanesulfonic acid, octanesulfonic acid, allylsulfonic acid, 1,1,2,2-tetrafluoroethanesulfonic acid, nonafluorobutanesulfonic acid, trifluoromethanesulfonic acid, p-toluenesulfonic acid, aminoacetic acid, trifluoroacetic acid, 2-hydroxy-2-phenylacetic acid, 2-aminopropionic acid, thiosalicylic acid, thiocyanic acid, dicyandiamide, dimethylphosphonic acid, diethylphosphonic acid, dibutylphosphonic acid, bis(2,4,4-trimethylpentyl)phosphonic acid, hexafluorophosphoric acid, tetrafluoroboric acid, hexafluoroantimonic acid, acid), tetrachloroaluminic acid, tetrachloroiron(III) salt, tris[(trifluoromethyl)sulfonyl]methane, bis(fluorosulfonyl)imide, bis(trifluoromethylsulfonyl)imide, and bis(pentafluoroethylsulfonyl)imide.

[0015] According to the present disclosure, it is possible to provide a solid electrolytic capacitor capable of improving its apparent capacitance ratio, and to provide a method for manufacturing such a solid electrolytic capacitor.

[0016] The above and other objects, features and advantages of the present disclosure will be more fully understood from the detailed description given below and the accompanying drawings, which are given by way of illustration only and are not to be considered as limiting the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1is a cross-sectional view of a solid electrolytic capacitor according to an embodiment;

[0018] Figure 2 is a cross-sectional view showing an example of a solid electrolyte layer provided in a solid electrolytic capacitor according to the embodiment;

[0019] Figure 3 is a flowchart for explaining a method for manufacturing a solid electrolytic capacitor according to an embodiment;

[0020] Figure 4 is a schematic diagram for explaining a method for manufacturing a first electrolyte layer (manufacturing method A);

[0021] Figure 5 is a schematic diagram for explaining a method for producing a first electrolyte layer (production method B); and

[0022] Figure 6 is a schematic diagram for explaining a method for producing a first electrolyte layer (production method C). DETAILED DESCRIPTION

[0023] <Solid electrolytic capacitors>

[0024] Hereinafter, embodiments will be described with reference to the accompanying drawings.

[0025] Figure 1 is a cross-sectional view of a solid electrolytic capacitor according to an embodiment. Figure 1 As shown, the solid electrolytic capacitor 1 according to the present embodiment includes an anode member 11, a dielectric layer 12, a solid electrolyte layer 13, a cathode layer 16, a conductive adhesive 17, an anode lead 18, an outer resin 19, and lead frames 20a and 20b.

[0026] The anode member 11 is made of a porous valve metal. For the anode member 11, for example, at least one metal selected from tantalum (Ta), aluminum (Al), niobium (Nb), titanium (Ti), zirconium (Zr), hafnium (Hf) and tungsten (W) or an alloy of these metals can be used. In particular, for the anode member 11, at least one metal selected from tantalum (Ta), aluminum (Al) and niobium (Nb) or an alloy of these metals is preferably used. The anode member 11 is formed by using, for example, a plate-shaped, foil-shaped or wire-shaped valve metal, a sintered body containing fine particles of valve metal, or a porous valve metal that has been subjected to surface expansion treatment by etching.

[0027] The dielectric layer 12 is formed on the surface of the anode member 11. For example, the dielectric layer 12 can be formed by anodizing the surface of the anode member 11. For example, the surface of the anode member 11 is porous, and the dielectric layer 12 is also formed in the pores of the porous anode member 11. For example, when tantalum is used as the anode member 11, a tantalum oxide film (dielectric layer 12) can be formed on the surface of the anode member 11 by anodizing the anode member 11. For example, the thickness of the dielectric layer 12 can be appropriately adjusted by the voltage in the anodizing process.

[0028] The solid electrolyte layer 13 is formed on the dielectric layer 12. The solid electrolyte layer 13 is formed so as to be in contact with the entire surface of the dielectric layer 12. The details of the solid electrolyte layer 13 will be described later.

[0029] The cathode layer 16 is formed on the solid electrolyte layer 13. The cathode layer 16 can be formed by laminating (ie, stacking) a carbon layer and a silver layer, for example. Note that the carbon layer and the silver layer are merely examples of materials forming the cathode layer 16, and the cathode layer is not limited to being formed of any specific material as long as the material is conductive (electrically conductive).

[0030] As described above, in the solid electrolytic capacitor 1 according to the present embodiment, the dielectric layer 12, the solid electrolyte layer 13 and the cathode layer 16 are sequentially laminated on the anode member 11. The anode member 11 includes the anode lead 18, and the anode lead 18 is connected to the lead frame 20a. For example, the anode lead 18 is connected to the lead frame 20a by welding. In addition, the cathode layer 16 is connected to the lead frame 20b by a conductive adhesive 17. The solid electrolytic capacitor 1 according to the present embodiment is covered with an outer resin 19, in which state parts of the two lead frames 20a and 20b are exposed to the outside.

[0031] <Structure of Solid Electrolyte Layer>

[0032] Next, the details of solid electrolyte layer 13 provided in solid electrolytic capacitor 1 according to the present embodiment will be described. Figure 2 is a cross-sectional view showing an example of a solid electrolyte layer provided in a solid electrolytic capacitor according to an embodiment, and is Figure 1 1 is an enlarged cross-sectional view of a portion of a solid electrolytic capacitor 1 including a dielectric layer 12 and a solid electrolyte layer 13 shown in FIG.

[0033] like Figure 2 As shown, the solid electrolyte layer 13 includes a first electrolyte layer 21 and a second electrolyte layer 22. The first electrolyte layer 21 is formed on the dielectric layer 12. The first electrolyte layer 21 is an ion-conducting electrolyte layer, and the second electrolyte layer 22 is an electron-conducting electrolyte layer.

[0034] In the present embodiment, the first electrolyte layer 21 includes, for example, a material represented by formula (1) shown below.

[0035] [Formula 1]

[0036]

[0037] Note that M in the formula (1) shown above represents a valve metal atom. That is, M is a valve metal atom constituting the anode member 11, specifically, a valve metal atom contained in the dielectric layer 12. For example, when the anode member 11 is composed of tantalum (Ta), the dielectric layer 12 is tantalum oxide (Ta2O5), and M is a tantalum atom.

[0038] In the formula (1) shown above, R 1+ a functional group representing at least one type of cation selected from the group consisting of imidazolium derivatives, pyrrolidinium derivatives, piperidinium derivatives, pyridinium derivatives, morpholinium derivatives, ammonium derivatives, derivatives and sulfonium derivatives, and R 1+ There is a carbon chain with a carbon number of 1 to 20 between the functional group of the cation and the Si molecule, and there is an ester bond, an ether bond, an amide bond, an imide bond, a carbon-carbon unsaturated bond, a carbon ring, or an interchain heterocyclic ring.

[0039] In the formula (1) shown above, R 2 represents one of the following: a hydrogen atom, a carbon chain having a carbon number of 1 to 4, a valve metal atom, or a polymer in which the materials represented by the formula (1) are polycondensed and connected to each other through -Si-O-Si-. Note that a polymer in which the materials represented by the formula (1) are connected through "-Si-O-Si-" is a polymer in which the materials adjacent to each other and "-OR 2 " are polycondensed with each other, and the respective materials represented by the formula (1) are connected to each other through "-Si-O-Si-".

[0040] In the formula (1) shown above, X- represents at least one type of anion selected from the group consisting of chloride, bromide, iodine, acetic acid, decanoic acid, sulfuric acid, lactic acid, nitric acid, benzoic acid, hydroxide, methyl sulfate, methanesulfonic acid, ethanesulfonic acid, octanesulfonic acid, allylsulfonic acid, 1,1,2,2-tetrafluoroethanesulfonic acid, nonafluorobutanesulfonic acid, trifluoromethanesulfonic acid, p-toluenesulfonic acid, aminoacetic acid, trifluoroacetic acid, 2-hydroxy-2-phenyl Acetic acid, 2-aminopropionic acid, thiosalicylic acid, thiocyanic acid, dicyandiamide, dimethylphosphonic acid, diethylphosphonic acid, dibutylphosphonic acid, bis(2,4,4-trimethylpentyl)phosphonic acid, hexafluorophosphonic acid, tetrafluoroboric acid, hexafluoroantimonic acid, tetrachloroaluminic acid, tetrachloroiron(III) salt, tris[(trifluoromethyl)sulfonyl]methane, bis(fluorosulfonyl)imide, bis(trifluoromethylsulfonyl)imide and bis(pentafluoroethylsulfonyl)imide.

[0041] Furthermore, in the first electrolyte layer 21, M in the above formula (1) is a valve metal atom present on the surface of the dielectric layer 12, and the first electrolyte layer 21 is covalently bonded to the surface of the dielectric layer 12 as shown by Si-OM (see Figures 4 to 6 ). Further, the first electrolyte layer 21 is in contact with the second electrolyte layer 22.

[0042] Furthermore, in the present embodiment, the electrical conductivity of the second electrolyte layer 22 is preferably higher than the electrical conductivity of the first electrolyte layer 21 .

[0043] The second electrolyte layer 22 is an electron conductive electrolyte layer and is composed of, for example, a conductive polymer. For the second electrolyte layer 22, for example, at least one type of conductive polymer is selected from the group consisting of polyethylene dioxythiophene (PEDOT), polypyrrole, polythiophene, polyaniline, and derivatives thereof. The second electrolyte layer 22 can be formed by using, for example, chemical polymerization, electrolytic polymerization, or by using a dispersion containing a conductive polymer or a liquid containing a conductive polymer.

[0044] In this embodiment, a third electrolyte layer (not shown) may be further formed on the second electrolyte layer 22. The third electrolyte layer may be formed by using, for example, a conductive polymer. For the third electrolyte layer, for example, at least one type of conductive polymer is selected from the group consisting of polyethylene dioxythiophene (PEDOT), polypyrrole, polythiophene, polyaniline, and their derivatives. The third electrolyte layer may be formed by using, for example, chemical polymerization, electrolytic polymerization, or by using a dispersion containing a conductive polymer or a liquid containing a conductive polymer. When forming the third electrolyte layer, the third electrolyte layer is preferably formed by using a method different from the method for forming the second electrolyte layer 22.

[0045] <Method of Manufacturing Solid Electrolytic Capacitor>

[0046] Next, a method for manufacturing a solid electrolytic capacitor according to the present embodiment will be described. Figure 3 is a flowchart for explaining a method for manufacturing a solid electrolytic capacitor according to the present embodiment. Figure 3 A method for making a solid electrolytic capacitor is described.

[0047] When manufacturing the solid electrolytic capacitor according to the present embodiment, first, anode member 11 is formed (step S1). A valve metal can be used for anode member 11. The above-mentioned materials can be used as the valve metal.

[0048] Next, the dielectric layer 12 is formed on the surface of the anode member (valve metal) 11 by anodizing the anode member 11 (step S2). Thereafter, the first electrolyte layer 21 is formed on the dielectric layer 12 (step S3). The material represented by the formula (1) shown above can be used for the first electrolyte layer 21. Note that the details of the method for forming the first electrolyte layer 21 will be described later.

[0049] Next, the second electrolyte layer 22 is formed on the first electrolyte layer 21 (step S4). The second electrolyte layer 22 can be formed by using, for example, a conductive polymer. For example, the second electrolyte layer 22 can be formed by using at least one type of conductive polymer selected from the group consisting of polyethylene dioxythiophene (PEDOT), polypyrrole, polythiophene, polyaniline, and derivatives thereof. The second electrolyte layer 22 can be formed by using chemical polymerization, electrolytic polymerization, or by using a dispersion containing a conductive polymer or a liquid containing a conductive polymer.

[0050] After forming the second electrolyte layer 22, the cathode layer 16 is formed (step S5). The cathode layer 16 can be formed by, for example, laminating (ie, stacking) a carbon layer and a silver layer.

[0051] Next, lead frames (electrodes) 20a and 20b are formed (step S6). Specifically, lead frame 20a is connected to anode lead 18 by welding. Furthermore, lead frame 20b is connected to cathode layer 16 by using conductive adhesive 17.

[0052] After that, the outer resin 19 is formed (step S7). Note that the outer resin 19 is formed so that parts of the two lead frames 20a and 20b are exposed to the outside. The resin used for the outer resin 19 is not limited to any specific resin. For example, a thermosetting epoxy resin or a method for curing a liquid resin can be used.

[0053] The solid electrolytic capacitor according to the present embodiment can be manufactured by using the above-described method for manufacturing a solid electrolytic capacitor.

[0054] <Method for Manufacturing First Electrolyte Layer 21>

[0055] Next, a method for producing the first electrolyte layer 21 will be described. Three production methods A to C will be described hereinafter as methods for producing the first electrolyte layer 21.

[0056] (Manufacturing method A)

[0057] First, the manufacturing method A of the first electrolyte layer 21 will be described. In the manufacturing method A, first, the alkoxy group OR of the ionic liquid represented by the formula (2) shown below (hereinafter also represented as RTIL (Room Temperature Ionic Liquid)) is hydrolyzed. 3 , thereby obtaining an ionic liquid containing a silanol group represented by the formula (3) shown below. Thereafter, the OH group bonded to the surface of the dielectric layer 12 and the silanol group represented by the formula (3) shown below are dehydrated and condensed, thereby fixing the material represented by the formula (1) shown above on the surface of the dielectric layer 12. Note that R in the formula (2) shown below 3 represents a carbon chain having a carbon number of 1 to 4. A more detailed description will be given hereinafter using a schematic diagram.

[0058] [Formula 2]

[0059]

[0060] [Formula 3]

[0061]

[0062] Figure 4 Schematic diagram for explaining a method for manufacturing a first electrolyte layer (manufacturing method A). Figure 4 As shown, in the manufacturing method A, the first electrolyte layer 21 is formed by using an RTIL material 30, which includes a silane coupling agent portion 31 and a salt portion 32 composed of anions and cations. The salt portion 32 contains a cationic functional group 33 and an anion 34. Note that the cationic functional group 33 corresponds to the “R 1+ ”, and anion 34 corresponds to “X-” of formulae (2) and (3) shown above.

[0063] In the manufacturing method A, the first electrolyte layer 21 is formed by the RTIL material 30, wherein the silane coupling agent part 31 and the salt part 32 are integrated (ie, combined) with each other. Specifically, Figure 4As shown in the lower part of FIG. 1 , the silane coupling agent portion 31 of the RTIL material 30 and the OH group present on the surface of the dielectric layer 12 undergo a silane coupling reaction therebetween, thereby fixing the silane coupling agent portion 31 in the surface of the dielectric layer 12. In this way, the salt portion 32 can be fixed to the surface of the dielectric layer 12 by using the silane coupling agent portion 31. Figure 4 In the structure shown in the lower part of , anions and cations are electrostatically bonded to each other in the salt portion 32, and the anions can move along the positive charge (ie, in the left / right direction in the figure).

[0064] (Manufacturing method B)

[0065] Next, the manufacturing method B of the first electrolyte layer 21 will be described. In the manufacturing method B, first, the alkoxy group of the amino silane coupling agent is hydrolyzed to obtain the amino silane coupling agent containing a silanol group. Then, the OH group bonded to the surface of the dielectric layer 12 and the silanol group of the amino silane coupling agent are dehydrated and condensed to fix the amino silane coupling agent on the surface of the dielectric layer 12. Thereafter, the anion X - The acid and / or salt of the amino silane coupling agent is contacted with the amino silane coupling agent, and they react with the amino group and the anion X - As a result, a material represented by the formula (1) shown above is formed. A more detailed description will be given below by using schematic diagrams.

[0066] Figure 5 Schematic diagram for explaining the method for manufacturing the first electrolyte layer (manufacturing method B). Figure 5 As shown, in the manufacturing method B, an amino-type silane coupling agent is first prepared. Then, the alkoxy group of the amino-type silane coupling agent is hydrolyzed, and thus an amino-type silane coupling agent containing a silane alcohol group is obtained. Figure 5 As shown in the upper half of , the OH groups bonded to the surface of the dielectric layer 12 and the silanol groups of the amino silane coupling agent are dehydrated and condensed, thereby fixing the amino silane coupling agent 40 to the surface of the dielectric layer 12 through covalent bonds.

[0067] Afterwards, if Figure 5 As shown in the central part of the diagram, an amino silane coupling agent 40 and a phosphoric acid 41 (H2PO4 - ) of salt. Next, Figure 5 As shown in the lower part of the figure, the ions of phosphoric acid 41 and the ions of RTIL anions 42 are exchanged. The residues (phosphoric acid, etc.) in this process are washed away with ethanol. In this way, the RTIL anions 42 can be fixed on the surface of the dielectric layer 12. Figure 5In the structure shown in the lower part of FIG. 4 , the amino-type silane coupling agent 40 and the RTIL anion 42 are electrostatically bonded to each other, and the RTIL anion 42 is capable of moving positive charges (i.e., in the left / right direction in the figure). The RTIL anion 42 that exchanges ions with the phosphoric acid 41 may be any anion that can constitute the RTIL. When the RTIL anion 42 is bonded to the amino-type silane coupling agent 40 and the phosphoric acid 41 (H2PO4 - ) and exchange their ions, they may be in the form of RTILs. Alternatively, a salt solution containing anions capable of constituting RTILs (i.e. a salt that is solid at room temperature and in which the cation is a Li, K or Na ion) may be used.

[0068] (Manufacturing method C)

[0069] Next, the manufacturing method C of the first electrolyte layer 21 will be described. In the manufacturing method C, first, the alkoxy group of at least one silane coupling agent selected from the group consisting of an amino-type silane coupling agent, an epoxy-type silane coupling agent, and a thiol-type silane coupling agent is hydrolyzed to obtain a silane coupling agent containing a silanol group. Thereafter, the OH group bonded to the surface of the dielectric layer 12 and the silanol group of the silane coupling agent are dehydrated and condensed, thereby fixing the amino-type silane coupling agent to the surface of the dielectric layer 12 by a covalent bond.

[0070] Then, the RTIL containing the epoxy group represented by the formula (4) shown below is brought into contact with the silane coupling agent fixed to the surface of the dielectric layer 12, and then the RTIL and the silane coupling agent are heated. As a result, the epoxy group represented by the formula (4) shown below is bonded to the amino group, epoxy group or thiol group of the silane coupling agent, thereby forming the material represented by the formula (1) shown above. A more detailed description will be given below using schematic diagrams.

[0071] [Formula 4]

[0072]

[0073] Figure 6 Schematic diagram for explaining a method for manufacturing a first electrolyte layer (manufacturing method C). Figure 6 As shown in the upper part of , a material 50 including a silane coupling agent portion 51 and an organic reaction portion 52 is used in the manufacturing method C. Note that the organic reaction portion 52 is an amino group, an epoxy group, or a thiol group. In the manufacturing method C, the silane coupling agent portion 51 of the material 50 and the OH group present on the surface of the dielectric layer 12 undergo a silane coupling reaction (dehydration and condensation) therebetween, thereby fixing the silane coupling agent portion 51 to the surface of the dielectric layer 12.

[0074] Afterwards, if Figure 6As shown in the lower part of FIG, the RTIL 53 containing the epoxy group 54 is brought into contact with the material 50 fixed on the surface of the dielectric layer 12, and then the material and the RTIL are heated. As a result, the epoxy group 54 is bonded to the organic reaction part 52 of the material. In this way, the RTIL 53 can be fixed on the surface of the dielectric layer 12. Figure 6 In the structure shown in the lower part of , anions and cations are electrostatically bonded to each other, and the anions are able to move positive charges (i.e., in the left / right direction in the figure).

[0075] By using any one of the above-described manufacturing methods A to C, the first electrolyte layer 21 may be formed on the surface of the dielectric layer 12 .

[0076] Note that in the present embodiment, as described above, a third electrolyte layer may be further formed on the second electrolyte layer 22. The third electrolyte layer may be formed by using, for example, a conductive polymer. For the third electrolyte layer, for example, at least one type of conductive polymer is selected from the group consisting of polyethylene dioxythiophene (PEDOT), polypyrrole, polythiophene, polyaniline, and derivatives thereof. The third electrolyte layer may be formed by using, for example, chemical polymerization, electrolytic polymerization, or by using a dispersion containing a conductive polymer or a liquid containing a conductive polymer. When forming the third electrolyte layer, the third electrolyte layer is preferably formed by using a method different from the method for forming the second electrolyte layer 22.

[0077] As described above, the solid electrolytic capacitor according to the present embodiment includes the first electrolyte layer 21 and the second electrolyte layer 22 as the solid electrolyte layer 13. The first electrolyte layer 21 is an ion conductive electrolyte layer, and the second electrolyte layer 22 is an electron conductive electrolyte layer. That is, since the first electrolyte layer 21 is densely formed on the dielectric layer 12, and the second electrolyte layer 22 showing good conductive characteristics is formed on the first electrolyte layer 21, the capacitance apparent ratio of the solid electrolytic capacitor can be improved.

[0078] Furthermore, as described above, in the present embodiment, the first electrolyte layer 21 including the salt portion composed of anions and cations derived from RTIL is fixed to the surface of the dielectric layer 12. Therefore, it is possible to prevent the RTIL from flowing out from the solid electrolyte layer 13, thereby preventing the characteristics of the solid electrolyte layer 13 from being deteriorated due to the outflow of the RTIL.

[0079] That is, when an ionic liquid is used as a solid electrolyte, there is a risk that the ionic liquid can flow out of the solid electrolyte layer 13. For example, if the ionic liquid flows out of the solid electrolyte layer 13 to the lead frame, the characteristics of the solid electrolytic capacitor may deteriorate due to the outflow of ions from the liquid (for example, the leakage current (LC) may increase). In contrast, in the present embodiment, the first electrolyte layer 21 containing the ionic liquid is fixed to the surface of the dielectric layer 12 by using a silane coupling agent or the like. Therefore, the outflow of the ionic liquid of the solid electrolyte layer 13 can be prevented, thereby preventing the characteristics of the solid electrolyte layer 13 from being deteriorated due to the outflow of the ionic liquid.

[0080] Example

[0081] Hereinafter, the present disclosure will be described in more detail based on examples. However, the present disclosure is not limited to these examples.

[0082] <Example 1>

[0083] As a sample according to Example 1, a sample was manufactured in which Figure 4 ) forms the first electrolyte layer 21.

[0084] Specifically, the capacitor element is formed by anodizing a sintered body made of tantalum fine powder (serving as a valve metal) at 50 V in a phosphoric acid aqueous solution and forming a dielectric layer 12 made of tantalum oxide on the entire surface of the sintered body made of the tantalum fine powder.

[0085] Next, by the above-mentioned manufacturing method A (see Figure 4 ) A first electrolyte layer 21 is formed on the dielectric layer 12. In Example 1, alkylamine-TFSI into which a methoxysilyl group is introduced is used as the RTIL material 30, in which a silane coupling agent part 31 and a salt part 32 are integrated (ie, combined) with each other.

[0086] Next, the second electrolyte layer 22 is formed by chemical polymerization. Specifically, an oxidant and a monomer for forming a conductive polymer (3,4-ethylenedioxythiophene) are reacted with each other on the first electrolyte layer 21. After that, the unreacted oxidant and monomer are washed with water or ethanol. The above operation is repeated multiple times, thereby forming a conductive polymer layer (second electrolyte layer) on the first electrolyte layer 21.

[0087] After forming the second electrolyte layer 22, a carbon layer is formed by immersing a pellet in a carbon slurry, pulling out the pellet from the carbon slurry, and drying the pellet at 120° C. for 1 hour. After forming the carbon layer, a silver layer is formed by immersing the pellet in a silver slurry, pulling out the pellet from the silver slurry, and drying the pellet at 120° C. for 1 hour. Next, the valve metal lead and the electrode are welded and connected. In addition, the silver layer and the electrode are connected to each other by using a conductive adhesive. Then, a solid electrolytic capacitor is manufactured by forming an external resin.

[0088] <Examples 2 to 5>

[0089] As samples according to Examples 2 to 5, samples were manufactured, in each of which the above-mentioned manufacturing method B (see Figure 5 ) to form the first electrolyte layer 21. Note that, except that the first electrolyte layer 21 is formed by the manufacturing method B, each of Examples 2 to 5 is the same as Example 1.

[0090] In Example 2, KBM-903 (amino type, hydrophilic type, manufactured by Shin-Etsu Chemical Co., Ltd.) was prepared as Figure 5 The amino silane coupling agent 40 is shown. Then, the alkoxy group of the amino silane coupling agent is hydrolyzed to obtain an amino silane coupling agent containing a silanol group. Then, the OH group bonded to the surface of the dielectric layer 12 and the silanol group of the amino silane coupling agent are dehydrated and condensed, so that the amino silane coupling agent 40 is fixed to the surface of the dielectric layer 12 by a covalent bond.

[0091] Then, if Figure 5 As shown in the central part of the diagram, an amino silane coupling agent 40 and a phosphoric acid 41 (H2PO4 - ) of salt. Next, Figure 5 As shown in the lower part of , 1-ethyl-3-methylimidazolium-bis(trifluoromethylsulfonyl)imide (EMI-TFSI) used as RTIL is brought into contact with a salt, so that the ions of phosphoric acid 41 and the ions of RTIL anion 42 are exchanged. Note that the RTIL anion 42 in this embodiment is bis(trifluoromethylsulfonyl)imide (TFSI). Further, the residues (phosphoric acid, etc.) in the process are washed away with ethanol. The first electrolyte layer 21 is formed by the above method. The rest of the manufacturing method is similar to the manufacturing method of Example 1.

[0092] Note that in Example 3, KBM-573 (amino type, hydrophobic type, manufactured by Shin-Etsu Chemical Co., Ltd.) was used as the amino type silane coupling agent 40. In Example 4, KBM-603 (amino type, hydrophilic type, manufactured by Shin-Etsu Chemical Co., Ltd.) was used as the amino type silane coupling agent 40, and 1-ethyl-3-methylimidazolium-ethylsulfonate (EMI-ES) was used as the RTIL. Note that the RTIL anion 42 in this example is ethylsulfonate (ES). In Example 5, KBM-6803 (amino type, hydrophobic type, manufactured by Shin-Etsu Chemical Co., Ltd.) was used as the amino type silane coupling agent 40, and 1-butyl-3-methylpyridinium-bis(fluorosulfonyl)imide (BMP-FSI) was used as the RTIL. Note that the RTIL anion 42 in this example is bis(fluorosulfonyl)imide (FSI). The samples according to Examples 3 to 5 were manufactured by the above-mentioned manufacturing method, wherein the rest of the manufacturing method is similar to the manufacturing method of Example 2.

[0093] <Examples 6 to 10>

[0094] As samples according to Examples 6 to 10, samples were manufactured, in each of which the above-mentioned manufacturing method C (see Figure 6 ) to form the first electrolyte layer 21. Note that each of Examples 6 to 10 is the same as Example 1 except that the first electrolyte layer 21 is formed by the manufacturing method C.

[0095] In Example 6, KBM-403 (glycidyl type, manufactured by Shin-Etsu Chemical Co., Ltd.) was prepared as Figure 6 The material 50 shown has a silane coupling agent portion 51 and an organic reaction portion 52. KBM-403 contains an epoxy group as the organic reaction portion 52. In Example 6, the silane coupling agent portion 51 of KBM-403 and the OH group present on the surface of the dielectric layer 12 are subjected to a silane coupling reaction (dehydration and condensation) therebetween, thereby fixing the silane coupling agent portion 51 to the surface of the dielectric layer 12.

[0096] Afterwards, if Figure 6As shown in the lower part of the embodiment, the ionic liquid 53 containing the epoxy group 54 (alkylamine-TFSI into which the epoxy group is introduced) is contacted with the KBM-403 fixed on the surface of the dielectric layer 12, and then heated. As a result, the epoxy group 54 is bonded to the organic reaction part 52 (epoxy group) of the silane coupling agent. The first electrolyte layer 21 is formed by the above method. The rest of the manufacturing method is similar to the manufacturing method of Example 1.

[0097] Note that in Example 7, KBM-903 (amino type, hydrophilic type, manufactured by Shin-Etsu Chemical Co., Ltd.) was used as Material 50. In Example 8, KBM-573 (amino type, hydrophobic type, manufactured by Shin-Etsu Chemical Co., Ltd.) was used as Material 50. In Example 9, KBM-603 (amino type, hydrophilic type, manufactured by Shin-Etsu Chemical Co., Ltd.) was used as Material 50. In Example 10, KBM-6803 (amino type, hydrophobic type, manufactured by Shin-Etsu Chemical Co., Ltd.) was used as Material 50. The samples according to Examples 7 to 10 were manufactured by the above-mentioned manufacturing method, wherein the rest of the manufacturing method was similar to the manufacturing method of Example 6.

[0098] <Comparative Example 1>

[0099] As a sample according to Comparative Example 1, a sample was formed in which the first electrolyte layer was formed by using KBM-403 (glycidyl type, manufactured by Shin-Etsu Chemical Co., Ltd.). Specifically, the silane coupling agent layer was formed by allowing the silane coupling agent portion of KBM-403 and the OH group present on the surface of the dielectric layer to undergo a silane coupling reaction (dehydration and condensation) therebetween, thereby fixing the silane coupling agent portion on the surface of the dielectric layer. The rest of the manufacturing method is similar to that of Example 1.

[0100] <Comparative Example 2>

[0101] As a sample according to Comparative Example 2, a sample was formed in which the first electrolyte layer was formed by using KBM-403 (glycidyl type, manufactured by Shin-Etsu Chemical Co., Ltd.) and EMI-TFSI. Specifically, the silane coupling agent portion of KBM-403 and the OH group present on the surface of the dielectric layer were subjected to a silane coupling reaction (dehydration and condensation) therebetween, thereby fixing the silane coupling agent portion to the surface of the dielectric layer. Thereafter, the first electrolyte layer 21 was formed by contacting the KBM-403 fixed to the surface of the dielectric layer 12 with the EMI-TFSI. The rest of the manufacturing method is similar to the manufacturing method of Example 1.

[0102] <Comparative Example 3>

[0103] As a sample according to comparative example 3, the sample is prepared by using KBM-403 and EMI-TFSI. Specifically, a silane coupling agent layer is formed by causing the silane coupling agent portion of KBM-403 to undergo a silane coupling reaction (dehydration and condensation) with the OH group present on the surface of the dielectric layer, thereby fixing the silane coupling agent portion on the surface of the dielectric layer. Then, the oxidant is reacted with the monomer 3,4-ethylenedioxythiophene for forming a conductive polymer. Afterwards, the unreacted oxidant and monomer are washed with water or ethanol. The above operation is repeated several times to form a conductive polymer layer on the first electrolyte layer 21. Afterwards, the obtained capacitor element is immersed in 1-ethyl-3-methylimidazolium-bis(trifluoromethylsulfonyl)imide (EMI-TFSI) used as an ionic liquid for 10 minutes, kept at room temperature for 30 minutes, and washed with ethanol. Through this process, an electrolyte layer composed of a conductive polymer layer and 1-ethyl-3-methylimidazolium-bis(trifluoromethylsulfonyl)imide (ie, an ionic liquid) was formed. The rest of the manufacturing method was similar to that of Example 1.

[0104] <Sample Evaluation>

[0105] Each solid electrolytic capacitor manufactured as described above was mounted on an evaluation substrate by a reflow soldering process, and then their capacitor characteristics were evaluated (capacitance apparent ratio (Cap apparent ratio) and characteristic failure incidence rate were measured). Regarding the evaluation of the Cap apparent ratio, the capacitance C0 measured in a 40% sulfuric acid solution after forming a dielectric oxide film by electrolytic oxidation, and the capacitance C1 measured after the electrolytic capacitor was mounted on the evaluation substrate were calculated. That is, the Cap apparent ratio (%) was calculated by using the expression shown below.

[0106] Cap apparent ratio (%) = C1 / C0×100

[0107] Regarding the evaluation of the characteristic failure occurrence rate, 20 electrolytic capacitors were mounted on their respective evaluation boards and voltage was applied for 500 hours under the conditions of 85°C and 85% RH. Then, the characteristic failure occurrence rate was calculated based on the number of the 20 evaluated electrolytic capacitors and the number of electrolytic capacitors in which characteristic failures occurred.

[0108] The evaluation results of the samples are shown in Table 1. As shown in Table 1, in Examples 1 to 10, the Cap apparent ratio was 83% or more, which means that the results were satisfactory. Further, in Examples 1 to 10, the characteristic failure occurrence rate was 0%, which means that the results were satisfactory.

[0109] In contrast, the Cap apparent ratio of Comparative Example 1 was 80%, that is, low. The reason for this is considered to be due to the fact that no ionic liquid was contained in the first electrolyte layer in Comparative Example 1.

[0110] In addition, the Cap apparent ratio of Comparative Example 2 was 80%, which was the same as that of Comparative Example 1, i.e., low. The reason for this is considered to be due to the fact that in Comparative Example 2, since the ionic liquid was not fixed on the dielectric layer, the ionic liquid flowed out by the subsequent washing, so that the ionic liquid was not contained in the first electrolyte layer.

[0111] Meanwhile, the Cap apparent ratio of Comparative Example 3 was 93% or more, meaning that the result was satisfactory. However, the characteristic failure occurrence rate of Comparative Example 3 was 10%, that is, high. The reason for this was due to the fact that in Comparative Example 3, KBM-403 used as a silane coupling agent and EMI-TFSI used as RTIL were neither electrostatically coupled nor chemically coupled, causing RTIL to flow out of the first electrolyte layer during the evaluation.

[0112] Table 1

[0113]

[0114] It will be apparent from the disclosure thus described that the embodiments of the disclosure may be modified in many ways. These variations should not be regarded as departing from the spirit and scope of the disclosure, and all such modifications as would be obvious to one skilled in the art are intended to be included within the scope of the appended claims.

Claims

1. A solid electrolytic capacitor, comprising: an anode member made of valve metal; a dielectric layer formed over the anode member; as well as a solid electrolyte layer formed on the dielectric layer, Wherein, the solid electrolyte layer comprises: a first electrolyte layer formed on the dielectric layer; and a second electrolyte layer formed on the first electrolyte layer, The first electrolyte layer is an ion-conducting electrolyte layer, and the second electrolyte layer is an electron-conducting electrolyte layer.

2. The solid electrolytic capacitor according to claim 1, wherein: The first electrolyte layer includes a material represented by formula (1) shown below, [Formula 1] Wherein, M in the formula (1) shown above represents a valve metal atom; R 1+ a functional group representing at least one type of cation selected from the group consisting of imidazolium derivatives, pyrrolidinium derivatives, piperidinium derivatives, pyridinium derivatives, morpholinium derivatives, ammonium derivatives, derivatives and sulfonium derivatives, and R 1+ There is a carbon chain with a carbon number of 1 to 20 between the functional group of the cation and the Si molecule, and there is an ester bond, an ether bond, an amide bond, an imide bond, a carbon-carbon unsaturated bond, a carbon ring, or an interchain heterocycle; In the formula (1) shown above, R 2 represents one of the following: a hydrogen atom, a carbon chain having a carbon number of 1 to 4, a valve metal atom, or a polymer in which the materials represented by the formula (1) are each polycondensed and connected to each other through -Si-O-Si-; and In the formula (1) shown above, X- represents at least one type of anion selected from the group consisting of chloride, bromide, iodine, acetic acid, decanoic acid, sulfuric acid, lactic acid, nitric acid, benzoic acid, hydroxide, methyl sulfate, methanesulfonic acid, ethanesulfonic acid, octanesulfonic acid, allylsulfonic acid, 1,1,2,2-tetrafluoroethanesulfonic acid, nonafluorobutanesulfonic acid, trifluoromethanesulfonic acid, p-toluenesulfonic acid, aminoacetic acid, trifluoroacetic acid, 2-hydroxy-2-phenyl Acetic acid, 2-aminopropionic acid, thiosalicylic acid, thiocyanic acid, dicyandiamide, dimethylphosphonic acid, diethylphosphonic acid, dibutylphosphonic acid, bis(2,4,4-trimethylpentyl)phosphonic acid, hexafluorophosphoric acid, tetrafluoroboric acid, hexafluoroantimonic acid, tetrachloroaluminic acid, tetrachloroiron(III) salt, tris[(trifluoromethyl)sulfonyl]methane, bis(fluorosulfonyl)imide, bis(trifluoromethylsulfonyl)imide and bis(pentafluoroethylsulfonyl)imide.

3. The solid electrolytic capacitor according to claim 2, wherein: In the first electrolyte layer, M in formula (1) shown above is a valve metal atom present in the surface of the dielectric layer; the first electrolyte layer is covalently bonded to the surface of the dielectric layer as shown in Si-OM; and the first electrolyte layer is in contact with the second electrolyte layer.

4. The solid electrolytic capacitor according to claim 3, wherein: The electrical conductivity of the second electrolyte layer is higher than the electrical conductivity of the first electrolyte layer.

5. The solid electrolytic capacitor according to claim 1 or 2, wherein: The second electrolyte layer includes a conductive polymer.

6. A method for preparing a solid electrolytic capacitor, comprising: In a first step, a dielectric layer is formed on an anode member made of a valve metal; as well as The second step is to form a solid electrolyte layer on the dielectric layer; Wherein, the second step comprises: The third step is to form a first electrolyte layer on the dielectric layer; and The fourth step is to form a second electrolyte layer on the first electrolyte layer. Wherein, the third step includes forming a layer including a material represented by formula (1) shown below on the dielectric layer, [Formula 1] Wherein, M in the formula (1) shown above represents a valve metal atom; R 1+ a functional group representing at least one type of cation selected from the group consisting of imidazolium derivatives, pyrrolidinium derivatives, piperidinium derivatives, pyridinium derivatives, morpholinium derivatives, ammonium derivatives, derivatives and sulfonium derivatives, and R 1+ There is a carbon chain with a carbon number of 1 to 20 between the functional group of the cation and the Si molecule, and there is an ester bond, an ether bond, an amide bond, an imide bond, a carbon-carbon unsaturated bond, a carbon ring, or an interchain heterocycle; In the formula (1) shown above, R 2 represents one of the following: a hydrogen atom, a carbon chain having a carbon number of 1 to 4, a valve metal atom, or a polymer in which the materials represented by the formula (1) are each polycondensed and connected to each other through -Si-O-Si-; and In the above-mentioned formula (1), X - represents at least one type of anion selected from the group consisting of chloride, bromide, iodine, acetic acid, decanoic acid, sulfuric acid, lactic acid, nitric acid, benzoic acid, hydroxide, methyl sulfate, methanesulfonic acid, ethanesulfonic acid, octanesulfonic acid, allylsulfonic acid, 1,1,2,2-tetrafluoroethanesulfonic acid, nonafluorobutanesulfonic acid, trifluoromethanesulfonic acid, p-toluenesulfonic acid, aminoacetic acid, trifluoroacetic acid, 2-hydroxy-2-phenylacetic acid, 2-aminopropionic acid, thiosalicylic acid, thiocyanic acid, dicyandiamide, dimethylphosphonic acid, diethylphosphonic acid, dibutylphosphonic acid, bis(2,4,4-trimethylpentyl)phosphonic acid, hexafluorophosphoric acid, tetrafluoroboric acid, hexafluoroantimonic acid, tetrachloroaluminic acid, tetrachloroiron(III) salt, tris[(trifluoromethyl)sulfonyl]methane, bis(fluorosulfonyl)imide, bis(trifluoromethylsulfonyl)imide, and bis(pentafluoroethylsulfonyl)imide.

7. The method for preparing a solid electrolytic capacitor according to claim 6, wherein: The third step comprises: step A, hydrolyzing the alkoxy group OR of the ionic liquid represented by the formula (2) shown below 3 , thereby obtaining an ionic liquid containing a silanol group represented by formula (3) shown below, and then dehydrating and condensing the OH group bonded to the surface of the dielectric layer and the silanol group of formula (3) shown below, thereby fixing the material represented by formula (1) shown above in the surface of the dielectric layer, [Formula 2] [Formula 3] Among them, R in the formula (2) shown above 3 It indicates a carbon chain with carbon numbers from 1 to 4.

8. The method for preparing a solid electrolytic capacitor according to claim 6, wherein: The third step comprises: Step B, hydrolyzing the alkoxy group of the amino silane coupling agent to obtain an amino silane coupling agent containing a silanol group, and then dehydrating and condensing the OH group bonded to the surface of the dielectric layer and the silanol group of the amino silane coupling agent to fix the amino silane coupling agent on the surface of the dielectric layer; Step C, after step B, forming a salt of an amino silane coupling agent and phosphoric acid, contacting the salt with an anion X-, and - The ions are exchanged between the amino groups and the anion X - The electrical interaction therebetween bonds the salt and the anion X-together and forms the material represented by formula (1) shown above.

9. The method for preparing a solid electrolytic capacitor according to claim 6, wherein: The third step comprises: Step D, hydrolyzing the alkoxy group of at least one silane coupling agent selected from amino silane coupling agents, epoxy silane coupling agents and thiol silane coupling agents to obtain a silane coupling agent containing a silanol group, and then dehydrating and condensing the OH group bonded to the surface of the dielectric layer and the silanol group of the silane coupling agent, thereby fixing the silane coupling agent on the surface of the dielectric layer; Step E, after step D, bringing an ionic liquid containing an epoxy group represented by formula (4) shown below into contact with the silane coupling agent formed on the surface of the dielectric layer in step D, and then heating the ionic liquid and the silane coupling agent to bond the epoxy group represented by formula (4) shown below to the amino group, epoxy group or thiol group of the silane coupling agent, and forming a material represented by formula (1) shown above, [Formula 4] 10. The method for preparing a solid electrolytic capacitor according to claim 6, wherein: The fourth step includes a step of forming a conductive polymer on the first electrolyte layer by chemical polymerization or a dispersion containing a conductive polymer or a liquid containing a conductive polymer.

11. The method for preparing a solid electrolytic capacitor according to claim 10, further comprising a fifth step of forming a third electrolyte layer on the second electrolyte layer, wherein: The fifth step includes the step of forming the third electrolyte layer containing a conductive polymer on the second electrolyte layer by using a method selected from chemical polymerization, electrolytic polymerization, or by using a dispersion containing a conductive polymer or a liquid containing a conductive polymer, and the method used in the fifth step is different from the method used in the fourth step.